New insight into the structure of PuGaO3 from ab initio particle-swarm optimization methodology. Issue 45 (1st November 2018) - Li, Shichang; Ye, Xiaoqiu; Liu, Tao; Gao, Tao; Ma, Shenggui; Ao, Bingyun
Abstract : A systematic study of the phase stability, chemical bonding, and lattice dynamics properties of PuGaO3 is performed by means of unbiased particle-swarm optimization techniques combined with first-principles calculations. Abstract : A systematic study of the phase stability, chemical bonding, and lattice dynamics properties of PuGaO3 is performed by means of unbiased particle-swarm optimization techniques combined with first-principles calculations. Phase stability analyses, including total energy, formation enthalpy, mechanical stability, and lattice dynamics, indicate that the ground-state structure of PuGaO3 at ambient pressure belongs to the space group Pnma . The fat-band dispersions and chemical bonding analysis suggest that Pnma PuGaO3 is an indirect band gap semiconductor (2.46 eV at the PBEsol + U level) at the Γ point and the Pu–O and Ga–O bonds in Pnma PuGaO3 are dominated by the ionic interactions. By examining the phonon spectra and phonon DOS, we provide a detailed insight into the lattice dynamics and thermodynamic properties of PuGaO3 . In addition, the infrared absorption and Raman scattering spectra of PuGaO3 are predicted and further assigned at the center ( Γ point) of the first Brillouin zone.